Cost effectiveness of school-located influenza vaccination programs for elementary and secondary school children - Byung-Kwang Yoo; Stanley J. Schaffer; Sharon G. Humiston; Cynthia M. Rand; Nicolas P. N. Goldstein; Christina S. Albertin; Cathleen Concannon; Peter G. Szilagyi (BMC, 2019)
Abstract Background Studies have noted variations in the cost-effectiveness of school-located influenza vaccination (SLIV), but little is known about how SLIV's cost-effectiveness may vary by targeted age group (e.g., elementary or secondary school students), or vaccine consent process (paper-based or web-based). Further, SLIV's cost-effectiveness may be impacted by its spillover effect on practice-based vaccination; prior studies have not addressed this issue. Methods We performed a cost-effectiveness analysis on two SLIV programs in upstate New York in 2015-2016: (a) elementary school SLIV using a stepped wedge design with schools as clusters (24 suburban and 18 urban schools) and (b) secondary school SLIV using a cluster randomized trial (16 suburban and 4 urban schools). The cost-per-additionally-vaccinated child (i.e., incremental cost-effectiveness ratio (ICER)) was estimated by dividing the incremental SLIV intervention cost by the incremental effectiveness (i.e., the additional number of vaccinated students in intervention schools compared to control schools). We performed deterministic analyses, one-way sensitivity analyses, and probabilistic analyses. Results The overall effectiveness measure (proportion of children vaccinated) was 5.7 and 5.5 percentage points higher, respectively, in intervention elementary (52.8%) and secondary schools (48.2%) than grade-matched control schools. SLIV programs vaccinated a small proportion of children in intervention elementary (5.2%) and secondary schools (2.5%). In elementary and secondary schools, the ICER excluding vaccine purchase was $85.71 and $86.51 per-additionally-vaccinated-child, respectively. When additionally accounting for observed spillover impact on practice-based vaccination, the ICER decreased to $80.53 in elementary schools -- decreasing substantially in secondary schools. (to $53.40). These estimates were higher than the published practice-based vaccination cost (median = $25.50, mean = $45.48). Also, these estimates were higher than our 2009-2011 urban SLIV program mean costs ($65) due to additional costs for use of a new web-based consent system ($12.97 per-additionally-vaccinated-child) and higher project coordination costs in 2015-2016. One-way sensitivity analyses showed that ICER estimates were most sensitive to the SLIV effectiveness. Conclusions SLIV raises vaccination rates and may increase practice-based vaccination in primary care practices. While these SLIV programs are effective, to be as cost-effective as practice-based vaccination our SLIV programs would need to vaccinate more students and/or lower the costs for consent systems and project coordination. Trial Registration ClinicalTrials.gov NCT02227186 (August 25, 2014), updated NCT03137667 (May 2, 2017).